The Effect of Sugar Dose and Fermentation Time on the Quality of Sauerkreut as a Source of Probiotic - Ari, Ari Andani Nasution; Trisna, Ade; Julianti, Elisa (ANIMAL PRODUCTION, 2024)
This study aims to determine the effect of sugar dosage and fermentation time on the quality of sauerkraut as a source of probiotics. This study used an experimental method in a 3x3 factorial completely randomized design (CRD). The first factor is three treatments of sugar concentration (A), namely A1 (2%), A2 (3.5%), and A3 (5%). The second factor is three treatments of fermentation time (B), namely B1 (5 days), B2 (7 days), and B3 (9 days). The results showed that there was no interaction (P>0.05) between factor A and factor B in the water content, but the water content had a significant effect (P<0.05) separately in factor A and factor B. In total LAB, there was a very significant interaction (P<0.01) between factor A and factor B, and in factor A and factor B. In pH, there was a significant interaction (P<0.05) between factor A and factor B, but a very significant effect (P<0.01) in factor A and factor B. In acid content there was a significant interaction (P<0.05) between factor A and Factor B, but a very significant effect (P<0.01) on factor A and factor B. This study concludes that cabbage processed into sauerkraut can be used as a probiotic supplement. The addition of 3.5% sugar and 7-day fermentation resulted in 91.11% water content, 3.43 pH, 2.93% total acid, and 7.4 x 109 total LAB